Anomalous carrier dynamics and localization effects in nonpolar m-plane InGaN/GaN quantum wells at high temperatures. (October 2020) - Huang, Xuanqi; Li, Dongying; Su, Po-Yi; Fu, Houqiang; Chen, Hong; Yang, Chen; Zhou, Jingan; Qi, Xin; Yang, Tsung-Han; Montes, Jossue; Deng, Xuguang; Fu, Kai; et al.
Abstract: Nonpolar InGaN/GaN quantum wells (QWs) have gained significance for efficient light emitting since it eliminates polarization-related effects and allows for higher radiative capability. Although much progress has been made in analyzing carrier localization effects at cryogenic temperatures, carrier dynamics at above room temperatures are still not well understood. In this work, we have observed and explored anomalous carrier dynamics of two nonpolar m -plane InGaN/GaN QWs at high temperatures by combining scanning transmission electron microscopy (STEM) and photophysical characterization. Both experimental and theoretical results suggest that carrier lifetime in both samples increases with temperature in a certain range of temperature. However, the reduced integrity and uniformity of QWs make carriers more prone to the nonradiative Shockley-Reed-Hall recombination as temperature rises. Moreover, both acoustic and optical phonon scatterings dominate from 300 to 600 K through the analysis on the evolution of photoluminescence spectra. Overall, these detailed studies provide insights into approaches to evaluate carrier dynamics at elevated temperatures and improve emitting performance to further push the practical efficiency limit. Graphical abstract: Image 1 Highlights: The anomalous increasing carrier lifetime with temperature in nonpolar m-plane InGaN/GaN QWs above RT has been discovered and analyzed. Carrier dynamics is correlated with localization effects and both radiative and nonradiative recombinations. The phonon-induced linewidth broadening mechanisms have been analyzed by fitting temperature-dependent PL spectra.